2013
DOI: 10.1093/cercor/bht306
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Right Temporoparietal Junction in the Control of Imitation

Abstract: Controlling neural representations of the self and other people is fundamental to social cognition. Brain imaging studies have implicated the right temporoparietal junction (rTPJ) in this ability, but causal evidence for its role is lacking. A debate is also ongoing regarding whether the control of, or switching between, self and other representations is a specialized or domain-general process: the rTPJ's well-established role in reorienting attention supports a domain-general process, but a role specific to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
123
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 38 publications
20
123
2
1
Order By: Relevance
“…Neurostimulation studies from our lab and others further showed a causal role of the rTPJ in self-other distinction (Bardi, Gheza, & Brass, 2017;Hogeveen et al, 2014;Santiesteban, Banissy, Catmur, & Bird, 2012;Sowden & Catmur, 2015). Research has shown reduced TPJ, and sometimes also mPFC activity in ASD during self-other distinction across several domains, including mentalizing (Eddy, 2016;Kennedy & Courchesne, 2008;Murdaugh, Nadendla, & Kana, 2014;Pfeifer et al, 2013;Spengler et al, 2010), adding to accumulating evidence that the TPJ is a core region implicated in ASD (Chien, Lin, Lai, Gau, & Tseng, 2015;Fishman, Keown, Lincoln, Pineda, & Müller, 2014;Kana, Uddin, Kenet, Chugani, & Müller, 2014).…”
Section: Introductionsupporting
confidence: 52%
“…Neurostimulation studies from our lab and others further showed a causal role of the rTPJ in self-other distinction (Bardi, Gheza, & Brass, 2017;Hogeveen et al, 2014;Santiesteban, Banissy, Catmur, & Bird, 2012;Sowden & Catmur, 2015). Research has shown reduced TPJ, and sometimes also mPFC activity in ASD during self-other distinction across several domains, including mentalizing (Eddy, 2016;Kennedy & Courchesne, 2008;Murdaugh, Nadendla, & Kana, 2014;Pfeifer et al, 2013;Spengler et al, 2010), adding to accumulating evidence that the TPJ is a core region implicated in ASD (Chien, Lin, Lai, Gau, & Tseng, 2015;Fishman, Keown, Lincoln, Pineda, & Müller, 2014;Kana, Uddin, Kenet, Chugani, & Müller, 2014).…”
Section: Introductionsupporting
confidence: 52%
“…Training to increase self-other control improved both the control of imitation and visual perspective-taking. As noted above, however, both processes are known to rely on right TPJ [13,14]. A more stringent test of the involvement of self -other control across social cognitive domains is to measure whether training to increase self-other control in the motor domain affects a process that does not depend on the same neuroanatomical location, namely empathy.…”
Section: Training Self-other Control Across Social Cognitive Domainsmentioning
confidence: 99%
“…Most imaging studies have focused on this third alternative, namely on resolving conflict between observed and planned movements Spengler et al, 2010;). In particular, it has been shown that the temporoparietal junction (TPJ) and medial prefrontal cortex (MPFC) are involved in the imitation inhibition task, brain areas known to engage in self versus other representation Sowden & Catmur, 2013;Spengler et al, 2010;). This led researchers to relate a social function to these high-level processes dealing with self-other related conflict Santiesteban et al, 2012;Sowden & Catmur, 2013;Spengler et al, 2010;).…”
Section: Introductionmentioning
confidence: 99%